Detecting new microRNAs in human osteoarthritic chondrocytes identifies miR-3085 as a human, chondrocyte-selective, microRNA. Issue 3 (March 2016) - Crowe, N.; Swingler, T.E.; Le, L.T.T.; Barter, M.J.; Wheeler, G.; Pais, H.; Donell, S.T.; Young, D.A.; Dalmay, T.; Clark, I.M.
Summary: Objective: To use deep sequencing to identify novel microRNAs (miRNAs) in human osteoarthritic cartilage which have a functional role in chondrocyte phenotype or function. Design: A small RNA library was prepared from human osteoarthritic primary chondrocytes using in-house adaptors and analysed by Illumina sequencing. Novel candidate miRNAs were validated by northern blot and qRT-PCR. Expression was measured in cartilage models. Targets of novel candidates were identified by microarray and computational analysis, validated using 3′-UTR-luciferase reporter plasmids. Protein levels were assessed by western blot and functional analysis by cell adhesion. Results: We identified 990 known miRNAs and 1621 potential novel miRNAs in human osteoarthritic chondrocytes, 60 of the latter were expressed in all samples assayed. MicroRNA-140-3p was the most highly expressed microRNA in osteoarthritic cartilage. Sixteen novel candidate miRNAs were analysed further, of which six remained after northern blot analysis. Three novel miRNAs were regulated across models of chondrogenesis, chondrocyte differentiation or cartilage injury. One sequence (novel #11), annotated in rodents as microRNA-3085-3p, was preferentially expressed in cartilage, dependent on chondrocyte differentiation and, in man, is located in an intron of the cartilage-expressed gene CRTAC-1 . This microRNA was shown to target the ITGA5 gene directly (which encodes integrin alpha5) and inhibited adhesion to fibronectin (dependent on alpha5beta1 integrin). Conclusion: Deep sequencing has uncovered many potential microRNA candidates expressed in human cartilage. At least three of these show potential functional interest in cartilage homeostasis and osteoarthritis (OA). Particularly, novel #11 (microRNA-3085-3p) which has been identified for the first time in man.